Transformational Leadership of School Principals in Developing Islamic Education in Elementary Madrasahs - Evi Erfiyana; Ika Kartika; Opan Arifudin (Yayasan Azka Hafidz Maulana, 2026)
This study aims to describe and analyze the role of transformational leadership of principals in the development of Islamic education in Islamic elementary schools. The research approach used is a qualitative case study method in several Islamic elementary schools in a specific region. Data were collected through in-depth interviews, observations, and document studies, then analyzed thematically to identify patterns and meanings related to the characteristics and practices of transformational leadership applied by principals. The results show that principals who apply transformational leadership are able to motivate teachers and students, inspire a more progressive vision of Islamic education, and create a learning environment conducive to the development of Islamic character and competency. These findings emphasize the importance of the role of visionary and inspirational leaders in strengthening the development of Islamic education at the elementary level. This study contributes to the development of educational leadership theory and the practice of principal leadership in the context of Islamic education.